Product Quality Improvement in Local Food Industry - Delia, Joseph Madis (Universiti Malaysia Sarawak (UNIMAS), 2009)
Recognition of Product Quality Improvement on local bakery industry as an important factor holds the key to competitiveness in the market irrespective of the size of the company. Product Quality Improvement practices are primarily found in larger and multinational industry but little has been written or applied in local bakery industry. This project reports the results of a full survey conducted among baking industry for local bakery of Kuching, Sarawak. The survey is expected to reveal the level of awareness of product quality improvement in the local bakery industry via questionnaire. The implementation or Total Quality Management (TQM) 5 Basic Principle is also propose to help this industry to increase their awareness on product quality improvement. This proposal is based on the main problem identified, be the root of lack of awareness on product quality improvement. Bakery must be able to adopt product quality improvement to help them meet global challenge in the long run. Finally, this project culminates with a discussion and the general conclusions from the survey findings. The result finding is expected to be a powerful information to future research directions on local bakery industry in Kuching, Sarawak.